2023
DOI: 10.1093/tas/txad028
|View full text |Cite
|
Sign up to set email alerts
|

Supplement feed efficiency of growing beef cattle grazing native Campos grasslands during winter: a collated analysis

Abstract: Supplementing growing cattle grazing native subtropical Campos grasslands during winter improves the low, even negative, average daily weight gain (ADG) typical of extensive animal production systems in Uruguay. Nonetheless, to render the practice profitable it is crucial to control supplement feed efficiency (SFE), that is, the difference in ADG between supplemented and control animals (ADGchng) per unit of supplement dry matter (DM) intake. Little has been studied specifically on how SFE varies in these syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This SFE is defined as the difference or change in average daily gain (ADG) between supplemented (S) and control (C) animals (ADGchng, kg) per unit (kg) of supplement dry matter (DM) intake. In the preceding paper of this same series [6], the authors found an average SFE of 0.21 ± 0.1 ADGchng/kg supplement DM intake, from growing beef cattle grazing native grasslands in winter.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…This SFE is defined as the difference or change in average daily gain (ADG) between supplemented (S) and control (C) animals (ADGchng, kg) per unit (kg) of supplement dry matter (DM) intake. In the preceding paper of this same series [6], the authors found an average SFE of 0.21 ± 0.1 ADGchng/kg supplement DM intake, from growing beef cattle grazing native grasslands in winter.…”
Section: Introductionmentioning
confidence: 90%
“…Data were gathered from 15 supplementation trials carried out between 2004 and 2018 in which growing beef cattle grazing native Campos grasslands in Uruguay were supplemented during late autumn and winter. More details of the database compilation and the response and auxiliary variables of the database can be found in Cazzuli et al [6]. In this paper, only some of the trials (15) collated by these authors were used, because not all of the original 15 trials presented data in such detail that more than two phases were identifiable (i.e., only initial and final BW were available).…”
Section: Database Compilationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is unclear to what extent and on which variables does supplementation affect animal selectivity and sward structure, particularly on native grasslands. Particularly, little is known about these processes when animals graze stockpiled herbage of grasslands that combine cool and warm season species and thus constitute horizontally and vertically heterogeneous mixtures of green and dead tissue (Cazzuli et al, 2023; Núñez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is unclear to what extent and on which variables does supplementation affect animal selectivity and sward structure, particularly on native grasslands. Particularly, little is known about these processes when animals graze stockpiled herbage of grasslands that combine cool and warm season species and thus constitute horizontally and vertically heterogeneous mixtures of green and dead tissue (Cazzuli et al, 2023;Núñez et al, 2022). Some studies of foraging behaviour of ruminants have been carried out on native grasslands of the Pampa Biome (Da Trindade et al, 2012Gonçalves et al, 2009), but no studies have been conducted aiming to characterize successive grazing strata, nor its interaction with concentrate supplementation.…”
Section: Introductionmentioning
confidence: 99%